A sustainable outer Space for a future on Earth. Outer Space, space debris and technologies - Lucilla Spini (Agathón)
Satellites and space objects made life on Earth easier during the Covid-19 pandemic, thanks to the use of digital technologies that have enabled to maintain personal, social and work relationships. A complex system that is articulated in outer Space which appears clean and uncontaminated in the collective imagination, but which is crowded and polluted with space debris that can compromise much of the activities that we depend on. The paper analyzes this context from the point of view of international agreements on outer Space and recent activities pertaining the mitigation and remediation of space debris, towards promoting the issue of sustainability in outer Space with an integrated approach to sustainability on Earth, also to consider outer Space and its resources as ‘natural capital’ and ‘human environment’ within the 2030 Agenda.